The effect of birth type on quantitative characteristics in pre-weaned Bligon goats - Kurniawati, Novita (2019)
This study aimed to determine the effect of birth type on growth performance in Bligon goats. In total, 88 female Bligon kids kept on a farmer group in Yogyakarta were appraised for quantitative traits. The goat does were divided into two birth types, single and twin. The traits observed were birth weight (BW), weaning weight (WW), ADG (average daily gain), body length (BL), heart girth (HG), withers height (WH) and hip height (HH). Data were analyzed using T-test. The results indicated that birth type had a significant effect (p<0.05) on BW, BL, HG and WH at birth (mean values 2.65±0.36 kg, 32.12±3.92 cm, 34.17±3.1 cm and 34.73±2.75 cm in single born and 2.03±0.35 kg, 29.43±3.08 cm, 32.29±2.59 cm and 32.88±2.64 cm in twins respectively). Birth type also had a significant effect (p<0.05) on WW, HG, WH, and HH at weaning age (mean values 10.27±2.05 kg, 43.97±3.7 cm, 51.05.±4.65 cm, 49.41±4.50 cm and 51.65±4.54 cm in single born and 8.45±2.47 kg, 41.02±3.5.55 cm, 44.70±5.48 cm, 43.27±5.09 cm and 44.82±4.97 cm in twins respectively). The mean ADG in single born (71.31±26.09 g) was significantly (P<0.05) higher than that in twins (88.73±22.07 g). In conclusion, birth type affects quantitative characteristics in Bligon goats.